The fit of the South African National Defence Force male combat trousers - Laba, Angelica (My University, 2013)
This study was contracted by the African Warrior Project of the South African National Defence Force (SAND F), which focuses on the needs of the future soldier. Fit problems cause the wearers of these combat trousers physical discomfort during routine physical training as the trousers restrict movement. The goals of the study were to investigate problems experienced by the male soldiers regarding the fit of the combat trousers, and to make recommendations regarding possible fit solutions. The objectives of this study were to determine the nature of the fit complaints in terms of the wearer characteristics and activities related to aesthetic and functional aspects; to analyse the design of the combat trousers in terms of size, key dimensions, proportion, balance and ease to determine the source of the fit the problems; and to analyse the f1t of the combat trousers against the subjective fit preferences of the wearers, and objective fit opinions of an expert. The target population of the study was the male SANDF members in the target age group of the African Warrior Project, namely 18 to 35 years. The first sample group consisted of 60 SANDF members between the ages of 24 to 45 years. The second sample of 24 subjects was selected from the first sample group, using height and body shape as parameters. The methods included biographic profiling, focus group interviews, one-to-one interviews, motor tests, body and garment measuring, photographs, somatographs and pattern analysis. The findings indicate the possibility of an inadequate garment design in relation to specific wearer characteristics such as ethnicity and body shape. The complicated size designation system used, compounded by the waist as the only key dimension provided, contributed to the distribution of the incorrectly sized combat trousers to the wearers. Analysis of the design indicated that it does not adequately accommodate the body characteristics and fit preferences of the subjects, to ensure optimum functionality as well as an acceptable aesthetic appearance. These problems need to be addressed.
Thesis (M. Tech. (Fashion, Dept. of Visual Arts and Design)--Vaal University of Technology.
Keywords: Combat trousers; South African National Defence Force; African Warrior Project; 355.140968; Military uniforms -- South Africa